PERKEMBANGAN TEORI MASHLAHAH ‘IZZU AL-DÎN BIN ‘ABD AL-SALÂM DALAM SEJARAH PEMIKIRAN HUKUM ISLAM - Enden Haetami (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2015)
This paper explains that mashlahah is one of Islam law methods that is very dominantly used to the Ulamasin Islamic Jurisprudence. Even though the Koran and the Sunna are assumed as the primary sources of Islamic law (qath‘îy), there is a lot of famous ulama and Muslim scholars who placed mashlahah as the primary sources of Islamic jurisprudence. Moreover, even though the position of mashlahah is assumed zhanniy, butin various cases – especially in Islamic Private Law – it is seldom placed higher than the other methods such as ijma‘, qiyas, istihsân, istishhâb, syadd al-dzari‘ah, syar‘u man qablana, and ‘urf. He used a logical of law that everything from God can be referred to the sacred texts (Nash), and everything from human being can be solved by mashlahah.